2002
DOI: 10.1023/a:1024478523252
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our experience suggests that peritoneal dialysis can be achieved in a community-based nursing home. This requires a systematic training program for the LTCF personnel and the availability of a "dedicated" nephrology dialysis staff. This is crucial to the success of the program. It is important that patients, their families and ESRD care professionals are informed of the limited survival expectation particularly for very old and severely impaired patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Among the three other prospective studies, peritonitis rates were 1 episode per 10–15 patient-months, and these rates were reported to be higher than in the community 6,12 . In contrast, peritonitis rates from retrospective chart reviews ranged from 1 episode per 7 patient-months to 1 episode per 40 patient-months 8,9,20 . Direct comparisons of these rates are limited by variation in assessment of peritonitis and study design (prospective vs. retrospective), as well as differences in patient populations (Canadian vs. United States; NH characteristics; average length of stay).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Among the three other prospective studies, peritonitis rates were 1 episode per 10–15 patient-months, and these rates were reported to be higher than in the community 6,12 . In contrast, peritonitis rates from retrospective chart reviews ranged from 1 episode per 7 patient-months to 1 episode per 40 patient-months 8,9,20 . Direct comparisons of these rates are limited by variation in assessment of peritonitis and study design (prospective vs. retrospective), as well as differences in patient populations (Canadian vs. United States; NH characteristics; average length of stay).…”
Section: Resultsmentioning
confidence: 95%
“…The prospective studies included in this review suggest that that it is feasible to conduct PD in NHs with appropriate staff training and support 6,12,17,19 . While three studies found higher peritonitis rates in NH residents compared to in the community 6,8,12 , there are likely underlying differences in the health and comorbidities of these patients which explain at least part of the higher infection rate. These limitations also affect generalizability of data on hospitalization rates, exit site infections, and transitions to HD.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations